Dr. Gator / Hazirah Zulkefli ... [et al.]. - Zulkefli, Hazirah; Rosli, Miza Inani; Zainudin, Nur Zalifah; Che Sofian, Che Saidatul Nasuha (2025)
Dr. Gator, a dynamic footwear brand based in Klang, Selangor, Malaysia, is working to change global footwear by focusing on sustainability, customization and affordability. Dr. Gator specializes in eco friendly Crocs style clogs and customisable accessories, all to redefine the footwear market by fusing sustainability, fashion and innovation to suit the ever-changing tastes of today’s consumer. We offer our key offerings: The EcoClog, a Crocs style clog made from recycled and bio-based materials and a huge range of customizable accessories ranging from Crocs themed charms to seasonal designs. EcoClogs is the company’s main product, designed from recycled and bio-based materials, lightweight waterproof designs, with customizable options like interchangeable Jibbitz charms, and engraving services. Dr. Gator caters to eco-minded millennials and Gen Z consumers aged 18 to 35 alongside families and professionals looking for footwear that’s durable, versatile, and reasonably priced.